2011
DOI: 10.4236/fns.2011.28121
|View full text |Cite
|
Sign up to set email alerts
|

Beef Meat Allergy in Cow’s Milk Allergic Adults

Abstract: Milk has been recognized as a leading cause of food allergy in children; however, studies on cow's milk allergy (CMA) in adults are scanty. The known cross-reactivity of bovine serum albumin and bovine -globulin which are present in both milk and beef is recognized, so that, patients with allergy to cow's milk are often instructed to avoid beef. Our Objective was to determine the prevalence of allergy to beef meat in adult patients with allergy to cow's milk. Thirty adults with CMA were included in the study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A number of studies in patients with cow's milk allergy demonstrated that between 60 and 87.5% had specific IgE to beef. 23,24 However, a review of studies in infants with cow's milk allergy found that only 13-20% were also beef allergic; interestingly, in their own double-blind, placebo-controlled food challenge study, the authors found up to 92.9% of children with beef allergy had concomitant milk allergy. 25 It is not known how many dogs in the present study had confirmed cutaneous AFR.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies in patients with cow's milk allergy demonstrated that between 60 and 87.5% had specific IgE to beef. 23,24 However, a review of studies in infants with cow's milk allergy found that only 13-20% were also beef allergic; interestingly, in their own double-blind, placebo-controlled food challenge study, the authors found up to 92.9% of children with beef allergy had concomitant milk allergy. 25 It is not known how many dogs in the present study had confirmed cutaneous AFR.…”
Section: Discussionmentioning
confidence: 99%
“…Caseins comprise nearly 80% of total milk proteins, and β-lg and BSA nearly 3% each [12,13,14]. Cross-reactivity between BSA and other bovine proteins has been observed in milk and meat, suggesting that BSA is a potential allergen for CMA patients [15]. However, BSA is considered a minor allergen in CMA [16], whereas it is one of the most important allergens in beef allergy.…”
Section: Introductionmentioning
confidence: 99%